Antibacterial and hemostatic composite material and preparation method thereof

By coupling and grafting graphene oxide with kaolin nanotubes and cross-linking with chitosan, an antibacterial and hemostasis composite material was prepared, which solved the problem of single and defective functions of existing hemostasis materials, and achieved rapid hemostasis, antibacterial and healing promotion effects.

CN119499430AActive Publication Date: 2025-02-25BEOGENE BIOTECH GUANGZHOU

Patent Information

Application Number
CN202411618329.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing hemostatic materials have single functions or various defects, which cannot effectively meet the requirements of ideal hemostatic materials, such as poor hemostatic effect, poor tissue adhesion, high cost and lack of antibacterial ability.

Method used

An antibacterial and hemostatic composite material was prepared by coupling and grafting the release graphene oxide with kaolin nanotubes and cross-linking with chitosan. This material combines the hemostasis effect of inorganic kaolin nanotubes and the biocompatibility of organic chitosan, while using the photothermal effect of graphene to enhance antibacterial ability.

Benefits of technology

It achieves rapid hemostasis, antibacterial and promotes tissue healing effects, has excellent biocompatibility and mechanical properties, can effectively resist bacterial infections, and shows good hemostasis performance in deep and non-compressive bleeding scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499430A_ABST
    Figure CN119499430A_ABST
Patent Text Reader

Abstract

The invention relates to an antibacterial and hemostatic composite material and a preparation method thereof. The preparation method comprises the following steps: reacting exfoliated graphene oxide with KH560 at 60 DEG C to obtain coupled grafted graphene oxide EGO; then under the condition of intense stirring at 80 DEG C, enabling the kaolin nanotube to react with EGO (Ethylene Gallate Oxide), so as to obtain EGO-EK; and then reacting the chitosan solution with EGO-EK by using a cross-linking agent and a catalyst to obtain a uniform suspension, and freeze-drying. The hemostatic composite material disclosed by the invention has the advantages of bacterial infection resistance, difficulty in tissue adhesion with a wound surface, good mechanical property, photo-thermal effect, excellent biocompatibility and rapid hemostatic capability, and in addition, the hemostatic composite material can accelerate the healing of the bacterial infection wound surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to an antibacterial and hemostatic composite material and a preparation method thereof. Background Art

[0002] Uncontrollable bleeding can cause huge casualties and losses. Therefore, in order to increase the possibility of survival, timely and effective control of bleeding is crucial. However, without the help of hemostatic materials, the coagulation process itself cannot effectively stop bleeding in time. In this case, the development of antibacterial biomaterials that can effectively and quickly stop bleeding is of great significance for the treatment of trauma patients.

[0003] Ideal hemostatic materials should not only be able to quickly control excessive bleeding, but also have characteristics such as absorbability, biodegradability, non-antigenicity and biocompatibility. Although traditional gauze and bandages are simple to make, low-cost, have a certain hemostatic effect, and can be reused repeatedly, they have many disadvantages, such as easy breeding of bacteria, adhesion to the wound surface, and easy to cause secondary bleeding during dressing changes, and cause tissue damage and other problems. Therefore, with the advancement of technology, people continue to develop new hemostatic materials, polymer hemostatic materials: collagen (Col), gelatin (GE), chitosan (CS), etc. Inorganic hemostatic materials, including kaolin, zeolite and montmorillonite, are popular because of their high efficiency, operability, cost-effectiveness and minimal tissue reactivity. Among them, Combat Gauze (Z-Medica) is a kaolin-impregnated gauze.

[0004] However, most of the current hemostatic materials have single functions or various defects, and cannot meet the requirements of ideal hemostatic materials. For example, collagen has poor tissue adhesion, porous zeolite generates a lot of heat when absorbing water from the blood, causing wound inflammation, and chitosan hemostatic materials have the problems of being brittle and unable to bend, poor hemostatic effect, poor tissue adhesion and high cost. Inorganic hemostatic materials, such as zeolite, may cause thermal damage to surrounding tissues, and kaolin takes longer to control arterial bleeding. In addition, the inorganic hemostatic agents currently used are not suitable for deep and non-compressive bleeding, and they also have the problems of poor tissue adhesion and low biological activity.

[0005] Therefore, there is an urgent need to explore composite antibacterial hemostatic materials with excellent hemostatic effect, rapid expansion ability to fill the wound cavity, appropriate tissue adhesion to avoid detachment from the wound, superior biocompatibility, and good antibacterial ability to promote tissue healing. Summary of the invention

[0006] In view of the above-mentioned current technical deficiencies, the present invention provides an antibacterial and hemostatic composite material and a preparation method thereof.

[0007] The first aspect of the present invention provides a method for preparing an antibacterial and hemostatic composite material, comprising the steps of:

[0008] S1: firstly reacting the exfoliated graphene oxide with the coupling agent KH560 at 60°C to obtain coupled grafted graphene oxide EGO; then, reacting kaolin nanotubes with the EGO at 80°C under vigorous stirring to obtain kaolin nanotube coupled grafted graphene oxide EGO-EK;

[0009] S2 uses a cross-linking agent and a catalyst to react the chitosan solution with EGO-EK to obtain a uniform suspension, which is then freeze-dried to obtain the antibacterial and hemostatic composite material.

[0010] First, graphene and kaolin nanotubes are combined through coupling grafting, and then combined with the polymer hemostatic material chitosan through cross-linking to obtain an inorganic-organic composite hemostatic material. The photothermal effect of graphene can also be utilized. The synthesis method is simple and the price is low.

[0011] When kaolin nanotubes and graphene oxide are coupled, the heating temperature must be 80°C. If the heating temperature is too low, the coupling agent KH560 cannot be fully activated to graft graphene oxide and kaolin nanotubes together; if the temperature is too high, it is easy to cause water evaporation, which is not conducive to the reaction.

[0012] Furthermore, in step S1, the mass ratio of exfoliated graphene oxide to KH560 is 1:4; and the mass ratio of kaolin nanotubes to EGO is 1:1.

[0013] Furthermore, the exfoliated graphene oxide is prepared by the following method: mixing graphite powder with concentrated sulfuric acid, then adding phosphorus pentoxide and potassium permanganate in sequence, and then reacting in a water bath at 80°C to obtain graphite oxide; then, mixing the obtained graphite oxide with concentrated sulfuric acid, adding potassium dichromate, reacting at 35°C, and after the reaction is completed, adding 30% H2O2 solution dropwise under ice bath conditions to react to obtain graphene oxide; finally, ultrasonic exfoliation is performed to obtain the exfoliated graphene oxide.

[0014] Furthermore, the kaolin nanotubes are prepared by the following method: kaolin, dimethyl sulfoxide and distilled water are mixed and stirred at 60°C for reaction, filtered and dried to obtain a kaolin-DMSO complex; the obtained dry kaolin-DMSO complex is dispersed in methanol, sealed and ultrasonicated, and then centrifuged to obtain a kaolin-CH3OH complex wet sample; the kaolin-CH3OH wet sample is then dispersed in a hexadecyltrimethylammonium chloride methanol solution, vigorously stirred at room temperature for 10 to 14 hours, and finally transferred to a reactor, reacted at 140 to 160°C for 10 to 14 hours, and after cooling, centrifuged, washed and dried to obtain the kaolin nanotubes.

[0015] Using flaky kaolin as raw material, organic matter is inserted between its layers to weaken the hydrogen bonding effect between the layers and expand the distance between the layers, so that its structure is not sufficient to overcome the geometric stress and undergoes bending deformation, thereby generating tubular kaolin nanotubes, which have better hemostatic ability than layered kaolin.

[0016] Furthermore, the kaolin particle size is ≤150 μm.

[0017] Furthermore, the kaolin: dimethyl sulfoxide: distilled water: hexadecyltrimethylammonium chloride methanol solution = 10 g: 100 mL: 9 mL: 50 mL, and the concentration of the hexadecyltrimethylammonium chloride methanol solution is 1 mol / L.

[0018] Furthermore, in step S2, the mass ratio of chitosan:EGO-EK is 5:1-3.

[0019] Furthermore, the crosslinking agent is EDC (1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), and the catalyst is NHS (N-hydroxysuccinimide). The amount of EDC or NHS added is generally 0.2%-0.75% of the weight of chitosan, and in a preferred embodiment, according to the mass ratio, EDC: NHS = 1:1.

[0020] Furthermore, the chitosan M W =50000, pH value of chitosan solution = 6.5-7, concentration is 1wt%.

[0021] Another aspect of the present invention also provides an antibacterial and hemostatic composite material prepared by the preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The hemostatic material of the present invention combines the raw materials by cross-linking, and the synthesis method is safe and has no toxic side effects;

[0024] 2) The raw material modification method of the present invention is simple and can be made by itself through modification. The method is simple, cheap, safe and reliable;

[0025] 3) The hemostatic material of the present invention cross-links the polymer hemostatic material chitosan and the inorganic hemostatic kaolin, and adds graphene oxide. Compared with the traditional single-function hemostatic material, the functions of the polymer hemostatic material and the inorganic hemostatic material are combined, and the photothermal properties of graphene can be used in combination with photothermal therapy to further improve the antibacterial effect. The obtained composite material integrates the three functions of hemostasis, anti-inflammatory and antibacterial.

[0026] 4) The hemostatic composite material of the present invention has the advantages of resisting bacterial infection, not being prone to tissue adhesion with the wound surface, having good mechanical properties, photothermal effects, excellent biocompatibility and rapid hemostasis ability, and can also accelerate the healing of bacterially infected wound surfaces, providing a reference for the development of antibacterial, hemostatic and healing-promoting composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM analysis picture of an embodiment of the present invention;

[0028] Figure 2 The swelling water absorption test results of the embodiments of the present invention;

[0029] Figure 3 The compression performance test results of the embodiment of the present invention are as follows;

[0030] Figure 4 The in vitro antibacterial performance test results of the embodiments of the present invention;

[0031] Figure 5 The whole blood coagulation index evaluation result of the embodiment of the present invention;

[0032] Figure 6 This is an evaluation of the amount of bleeding and the time of hemostasis in the rat tail amputation injury model according to an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0034] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0035] The kaolin nanotubes (EK), graphene oxide (GO), kaolin nanotubes coupled with grafted graphene oxide (EGO-EK), and chitosan (CS) solutions used in the following examples were prepared by the following method:

[0036] (1) Preparation of kaolin nanotubes (EK)

[0037] First, kaolin was sieved through 100 mesh and set aside. 10 g of kaolin sieved through 100 mesh was placed in a mixed solution of 100 mL of dimethyl sulfoxide and 9 mL of distilled water, stirred at 60 ° C for 12 hours, filtered and separated, and dried at 60 ° C for 24 hours. The dried kaolin-DMSO complex was dispersed in a conical flask containing methanol and ultrasonicated for 4 hours in a sealed state. Then, a wet sample of kaolin-CH3OH complex was obtained by centrifugation. The wet kaolin-CH3OH sample was dispersed in 50 mL, 1 mol / L hexadecyltrimethylammonium chloride methanol solution, stirred vigorously at room temperature for 12 hours, and then transferred to a polytetrafluoroethylene-lined reactor, reacted at 150 ° C for 12 hours, centrifuged after cooling, and then washed several times with ethanol and distilled water, and dried and collected at 100 ° C to obtain dry kaolin nanotubes.

[0038] (2) Preparation of exfoliated graphene oxide (GO)

[0039] Add 6g of graphite powder to a 500mL flask containing concentrated sulfuric acid, and add phosphorus pentoxide and potassium permanganate to the flask in sequence while stirring. Place the flask in a water bath at 80°C, react for 4h, filter and dry to obtain graphite oxide. Add graphite oxide to 240mL of concentrated sulfuric acid, then add potassium dichromate, react at 35°C for 2h, transfer to a crushed ice container, and add 30% H2O2 solution dropwise. The color changes from dark brown to bright yellow, indicating that the oxidation is successful, centrifuge to pH=7, and dry at 30°C to obtain graphene oxide. Weigh 0.3g of graphene oxide powder and place it in a beaker containing 100mL of ultrapure water, sonicate for 4h, and obtain a 0.3% exfoliated graphene oxide solution.

[0040] (3) Preparation of kaolin nanotubes coupled to grafted graphene oxide (EGO-EK)

[0041] The prepared exfoliated graphene oxide solution was transferred to a round-bottom flask, and then γ-glycidyloxypropyltrimethoxysilane (coupling agent KH560) was added in a mass ratio of 1:4 to the exfoliated graphene oxide, and then reacted at 60°C for 8h to obtain coupling agent grafted graphene oxide (EGO).

[0042] Kaolin nanotubes were weighed in a mass ratio of 1:1 to exfoliated graphene oxide and fully dispersed in the solution. The mixture was vigorously stirred and reacted at 80° C. for 3 h, and then freeze-dried to obtain kaolin nanotube-coupled grafted graphene oxide (EGO-EK).

[0043] (4) Preparation of chitosan (CS) solution

[0044] Weigh MW = 50000 chitosan 2g was dissolved in 2% dilute acetic acid, stirred at 300r / min at room temperature for 2h, and allowed to stand for 12h to fully dissolve to obtain a chitosan solution with a concentration of 1%. The chitosan solution was adjusted to pH = 6.5-7 for use.

[0045] Example 1

[0046] This embodiment provides an antibacterial and hemostatic material CS, and the specific preparation method is as follows:

[0047] Add the crosslinking agent EDC and the catalyst NHS in equal weight ratio to the 1% CS solution, wherein the amount of EDC or NHS added is 0.2% of the weight of CS, and stir at 50°C for 30 minutes to obtain a uniform suspension.

[0048] The suspension was then poured into a mold, left to stand at 4°C for 12 h to eliminate bubbles, and then freeze-dried for 36 h to obtain a sponge scaffold.

[0049] Example 2

[0050] This embodiment provides an antibacterial and hemostatic composite material CS / EGO-EK, and the specific preparation method is as follows:

[0051] Weigh EGO-EK according to the mass ratio of CS:EGO-EK=5:1, dissolve it in 1% CS solution, and stir it at 50℃ for 30min to make it fully dissolved;

[0052] Then add the crosslinking agent EDC and the catalyst NHS in equal weight ratio, wherein the amount of EDC or NHS added is 0.2% of the weight of CS, and stir the reaction for 30 minutes to obtain a uniform suspension;

[0053] The suspension was then poured into a mold, left to stand at 4°C for 12 h to eliminate bubbles, and then freeze-dried for 36 h to obtain a sponge scaffold.

[0054] Example 3

[0055] This embodiment provides an antibacterial and hemostatic composite material CS / EGO-EK, and the specific preparation method is as follows:

[0056] Weigh EGO-EK according to the mass ratio of CS:EGO-EK=5:2, dissolve it in 1% CS solution, and stir it at 50℃ for 30min to make it fully dissolved;

[0057] Then add the crosslinking agent EDC and the catalyst NHS in equal weight ratio, wherein the amount of EDC or NHS added is 0.2% of the weight of CS, and stir the reaction for 30 minutes to obtain a uniform suspension;

[0058] The suspension was then poured into a mold, left to stand at 4°C for 12 h to eliminate bubbles, and then freeze-dried for 36 h to obtain a sponge scaffold.

[0059] Example 4

[0060] This embodiment provides an antibacterial and hemostatic composite material CS / EGO-EK, and the specific preparation method is as follows:

[0061] Weigh EGO-EK according to the mass ratio of CS:EGO-EK=5:3, dissolve it in 1% CS solution, and stir at 50°C for 30 minutes to fully dissolve it;

[0062] Then add the crosslinking agent EDC and the catalyst NHS in equal weight ratio, wherein the amount of EDC or NHS added is 0.2% of the weight of CS, and stir the reaction for 30 minutes to obtain a uniform suspension;

[0063] The suspension was then poured into a mold, left to stand at 4°C for 12 h to eliminate bubbles, and then freeze-dried for 36 h to obtain a sponge scaffold.

[0064] Example 5

[0065] This embodiment provides an antibacterial and hemostatic composite material CS / GO, and the specific preparation method is as follows:

[0066] Weigh GO according to the mass ratio of CS: EGO-EK = 5:2, dissolve it in 1% CS solution, and stir it at 50°C for 30 minutes to fully dissolve it;

[0067] Then add the crosslinking agent EDC and the catalyst NHS in equal weight ratio, wherein the amount of EDC or NHS added is 0.2% of the weight of CS, and stir the reaction for 30 minutes to obtain a uniform suspension;

[0068] The suspension was then poured into a mold, left to stand at 4°C for 12 h to eliminate bubbles, and then freeze-dried for 36 h to obtain a sponge scaffold.

[0069] Testing and analysis:

[0070] 1. SEM structural analysis of sponge scaffolds

[0071] Test method: 300 μL of the pre-freezing suspension was placed in a 48-well plate and freeze-dried at -80°C to obtain a freeze-dried composite sponge. The freeze-dried composite sponge was then pasted on a copper table with carbon conductive glue, gold was sprayed on the surface for 30 seconds, and the surface morphology was observed using a scanning electron microscope. The test conditions were: 5kV electron beam. Image software was used to perform statistical analysis on the pore size of the composite sponge.

[0072] Test samples: CS of Example 1, CS / EGO-EK of Examples 2-4.

[0073] The results are as follows Figure 1 As shown in the figure, the freeze-dried composite sponge has an interconnected macroporous structure with a pore size of about 50 μm. At the same time, with the increase of EGO-EK content, the pores gradually decrease and the structure becomes denser, which is mainly attributed to the increase of cross-linking degree and the influence of freeze drying.

[0074] 2. Swelling and water absorption performance test

[0075] Test method: Weigh the weight of the sponge scaffold sample with a balance, record it as M0. Place the sample material in PBS, swell for 0.5, 1, 2, 3, 4, 5, 6 hours, quickly absorb the surface water with filter paper, weigh and record the sample mass as Mw. The sample water absorption rate (X) is calculated according to the following formula:

[0076] X(%)=(Mw-M0) / M0×100%

[0077] Test samples: CS of Example 1, CS / EGO-EK of Examples 2-4.

[0078] Results: Combined Figure 1 It can be seen that the composite material is rich in porous network structure and has good water absorption capacity, which helps to better absorb blood and wound exudate, promote rapid hemostasis of wounds, and thus prevent bacterial infection. Figure 2 As shown, all the composite materials exhibited excellent water absorption performance, and swelled rapidly within 1 hour after absorbing water. 80% of the water absorption was basically completed within 1 hour. Then, after 5 hours of swelling after absorbing water, the water absorption rate reached a balanced state. Among them, the composite material CS / EGO-EK of Example 3 5:2 It has the best water absorption performance, and the water absorption rate reaches 1280% after swelling for 6 hours; it can fully meet the requirements of rapid expansion to fill the wound cavity.

[0079] 3. Compression performance

[0080] Test method: 400 μL of the pre-freeze-dried suspension was placed in a 48-well plate and dried in a freeze dryer to form a cylindrical sponge dressing with a diameter of 10 mm and a height of 7 mm. After being placed overnight in a constant humidity environment, the sponge dressing was compressed to 80% of its original height at a rate of 5 mm / min using a universal testing machine, and the relationship between the stress (MPa) and strain (%) of the sample was recorded to examine the longitudinal compressive strength of the material.

[0081] Test samples: CS of Example 1, CS / EGO-EK of Examples 2-4.

[0082] Results: In order to reduce the discomfort and pain of patients, hemostatic materials must have good compression properties when used on wounds. Therefore, the compression strain-stress curve is used to evaluate the mechanical strength of hemostatic materials. Figure 3 As shown in the figure, after adding EGO-EK, the compressive stress increases. When the sponge is 80% deformed, the compressive stress of the hemostatic materials prepared by adding EGO-EK in Examples 2-4 is all greater than 600Kpa, and the CS / EGO-EK 5:2 The highest. This indicates that the introduction of an appropriate amount of EGO-EK into the hemostatic material of the present invention can improve the compression strength. This indicates that the composite hemostatic material of the present invention has good mechanical properties and a certain supporting capacity, and has a high application value as a wound dressing.

[0083] 4. In vitro antibacterial performance test

[0084] Test method: After Escherichia coli and Staphylococcus aureus are revived and cultured to the logarithmic growth phase, centrifuged, and the bacteria are collected and resuspended in saline. The final bacterial concentration is 1×108CFU / mL. After adding 500μL of the corresponding suspension to a 24-well plate, UV light is used to solidify the gel. Add 500μL of saline to the control group. Then add 100μL of the diluted bacterial suspension and 1mL of sterile saline to each well, incubate at 37°C for 24 hours, spread on LB agar plates after gradient dilution, and count.

[0085] Test samples: CS of Example 1, CS / EGO-EK of Example 3, CS / GO of Example 5.

[0086] Result description: Figure 4 CS, CS / GO are shown in 、 CS / EGO-EK 、 CS / GO 、 +NIR, CS / EGO-EK+NIR in vitro antibacterial test results, where the NIR group used a power of 1.5W / cm 2 808nm near-infrared light irradiation.

[0087] It can be seen that the graphene oxide sheet itself has excellent antibacterial effect, mainly due to the following reasons: 1) There are a large number of oxygen-containing groups on graphene oxide, such as hydroxyl, carboxyl, carbonyl, etc. These groups can form hydrogen bonds with sugars or proteins that make up the cell wall, and then graphene oxide will wrap the cells to isolate them from the nutrient solution, so that the cells lack nutrients and die; 2) Graphene oxide can adsorb on bacteria, and its sharp edges can destroy the cell membrane, causing bacteria to break and die; 3). Graphene oxide can change the oxygen partial pressure in bacteria, causing the substances in the bacteria to be oxidized, destroying the internal composition of the bacteria, and causing the bacteria to die. After the introduction of EGO-EK, there is a certain synergistic antibacterial effect. At the same time, the photothermal conversion performance of graphene oxide under 808nm near-infrared laser irradiation, combined with near-infrared irradiation, can cause excessive heat to be generated inside the bacteria, further improving the sterilization rate.

[0088] 5. In vitro hemostatic properties

[0089] Test method: The hemostatic potential of the material was evaluated by a whole blood coagulation experiment. Specifically, the sponge scaffold sample was placed in a 37°C culture dish, and 100 μL of blood (containing 3.8wt% anticoagulant sodium citrate 1:9) and 20 μL of CaCl2 (0.2mol / L) solution were dispensed into the sponge. The sample was incubated at 37°C for 5 minutes, then added to 25mL of distilled water, gently shaken, and allowed to stand for 5 minutes. The absorbance value of each sample was then measured at 545nm using a UV spectrophotometer. The blank control group was prepared by adding 200 μL of blood to 25mL of distilled water. The formula for calculating the coagulation index (BCI) is: BCI (%) = [OD sample / OD control ]×100%, where OD sample is the sample absorbance value, OD control is the absorbance value of the blank group.

[0090] Test samples: CS of Example 1, CS / EGO-EK of Example 3, CS / GO of Example 5.

[0091] Results show that the whole blood coagulation index reflects the coagulation effect of the material. The lower the coagulation index, the better the coagulation effect. Figure 5As shown, the coagulation index of the hemostatic material with the addition of EGO-EK is significantly reduced, indicating that the introduction of kaolin nanotubes greatly enhances the coagulation ability of the material. At the same time, after deionized water is poured into the culture dish, Example 3 overflows the least red blood cells. The material CS / EGO-EK of these Example 3 has excellent coagulation ability, which mainly depends on its chemical composition and spatial structure. The interconnected microporous structure of the hemostatic sponge combined with chitosan significantly improves the blood absorption rate and red blood cell aggregation rate of the material. In addition, kaolin nanotubes are a kind of aqueous aluminosilicate mineral, which further activates the human coagulation cascade by activating coagulation factor XII (FXII). The two materials cooperate with each other to further enhance the hemostatic ability.

[0092] 6. In vivo hemostasis ability

[0093] Test method: Anesthetize rats with 3% (w / v) sodium pentobarbital (intraperitoneal injection, 30 mg / kg) for 3 minutes. After successful anesthesia, the rats were fixed in supine position on the operating table. Disinfect the rat's tail with 75% medicinal alcohol and cut it in the middle with surgical scissors. After 10 seconds of free bleeding, wipe off the flowing blood with sterile gauze, and then stick the composite material sponge to the wound. Press the sampling sponge lightly with your hand and start timing from this starting point. Observe the wound every 30 seconds until there is no bleeding within 30 seconds after removing the hemostatic material. Record the hemostasis time, weigh the sample weight after hemostasis, and calculate the amount of bleeding. The gelatin sponge was used as the control group, and the untreated group was used as the blank control. Blood loss (m BL ) is calculated as: BL =m2-m1, where m1 and m2 are the mass of the sample before and after hemostasis, respectively, in g.

[0094] Test samples: CS of Example 1, CS / EGO-EK of Example 3, CS / GO of Example 5.

[0095] Results: First, the hemostatic effect of the material was evaluated using a rat tail amputation model. Figure 6 (A) shows the photographs of bleeding on filter paper after hemostasis using different hemostatic materials. In the experimental group, CS / EGO-EK of Example 3 has the shortest hemostatic time, the least bleeding amount, and the best hemostatic performance.

[0096] There are several reasons that can explain the above results, including: a) the porous network structure gives the hemostatic material excellent blood absorption ability and concentrates coagulation factors to capture red blood cells and platelets, thereby accelerating the coagulation process; b) when kaolin nanotubes come into contact with blood, they quickly absorb smaller water molecules in the blood, activate coagulation factors, and activate the body's coagulation cascade reaction; c) positively charged chitosan comes into contact with negatively charged red blood cells, causing red blood cells to aggregate and adhere to the wound.

[0097] From the above, it can be seen that the antibacterial and hemostatic composite material of the embodiment of the present invention has improved swelling and water absorption performance, compression performance, antibacterial property, and in vitro and in vivo hemostatic performance by introducing EGO-EK into chitosan, and can further improve the antibacterial property by using photothermal effect. The composite material of the embodiment of the present invention has excellent hemostatic effect, can expand rapidly to fill the wound cavity, has suitable tissue adhesion, and excellent biocompatibility, and good antibacterial ability, and can promote tissue healing.

[0098] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0099] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an antibacterial and hemostatic composite material, characterized in that: Includes steps: S1: firstly reacting the exfoliated graphene oxide with KH560 at 60°C to obtain coupled grafted graphene oxide EGO; then, reacting kaolin nanotubes with the EGO at 80°C under vigorous stirring to obtain kaolin nanotube coupled grafted graphene oxide EGO-EK; S2 uses a cross-linking agent and a catalyst to react the chitosan solution with EGO-EK to obtain a uniform suspension, which is then freeze-dried to obtain the antibacterial and hemostatic composite material.

2. The preparation method according to claim 1, characterized in that: According to the mass ratio, in step S1, the exfoliated graphene oxide: KH560 = 1:4; kaolin nanotubes: EGO = 1:

1.

3. The preparation method according to claim 1, characterized in that: The exfoliated graphene oxide is prepared by the following method: mixing graphite powder with concentrated sulfuric acid, then sequentially adding phosphorus pentoxide and potassium permanganate, and then reacting in a water bath at 80° C. to obtain graphite oxide; Then, the obtained graphite oxide and concentrated sulfuric acid are mixed, and potassium dichromate is added to react at 35° C. After the reaction is completed, a 30% H2O2 solution is added dropwise in an ice bath to obtain graphene oxide; Finally, ultrasonic exfoliation is performed to obtain the exfoliated graphene oxide.

4. The preparation method according to claim 1, characterized in that: The kaolin nanotubes are prepared by the following method: Kaolin, dimethyl sulfoxide and distilled water are mixed and stirred at 60°C for reaction, filtered and dried to obtain a kaolin-DMSO complex; the obtained dry kaolin-DMSO complex is dispersed in methanol, sealed and ultrasonicated, and then centrifuged to obtain a kaolin-CH3OH complex wet sample; the kaolin-CH3OH wet sample is then dispersed in a hexadecyltrimethylammonium chloride methanol solution, vigorously stirred at room temperature for 10 to 14 hours, and finally transferred to a reactor, reacted at 140 to 160°C for 10 to 14 hours, and after cooling, centrifuged, washed and dried to obtain the kaolin nanotubes.

5. The preparation method according to claim 4, characterized in that: The kaolin particle size is ≤150 μm.

6. The preparation method according to claim 4, characterized in that: The kaolin: dimethyl sulfoxide: distilled water: hexadecyltrimethylammonium chloride methanol solution = 10 g: 100 mL: 9 mL: 50 mL, and the concentration of the hexadecyltrimethylammonium chloride methanol solution is 1 mol / L.

7. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio is chitosan:EGO-EK=5:1-3.

8. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking agent is EDC, and the catalyst is NHS.

9. The preparation method according to claim 1, characterized in that: In step S2, the chitosan M W =50000, pH value of chitosan solution = 6.5-7, concentration is 1wt%.

10. The antibacterial and hemostatic composite material prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of graphene kaolin composite nanometer rubber fillers

    CN103275524A

  • Preparation method of kaolin nanotube used for desulfurizer

    CN104475025A

  • Kaolin modified graphene material and preparation method thereof

    CN108130104A

  • Chitosan cross-linked graphene oxide composite sponge capable of efficiently stopping bleeding as well as preparation method and application of chitosan cross-linked graphene oxide composite sponge

    CN115926245A

  • Hemostatic Anti-infection wound dressing and preparation method thereof

    EP3669898A1

Cited By

  • Preparation method and application of kaolin-graphene quantum dot composite material

    CN121313913A

  • Preparation method and application of kaolin-graphene quantum dot composite material

    CN121313913B